A clinical study of spectrum of low platelet count to establish etiology, diagnosis, complications and prognosis in newborns admitted in Al-Ameen medical college hospital NICU, Bijapur, Karnataka, India - Zama, Rizwan U.; Malagi, Naushad Ali N.; Thobbi, A. N.; Dhundasi, Salim A. (International Journal of Contemporary Pediatrics, 2020)
Background: In the newborn low platelet count is a common finding in both preterm and term newborn. It has been estimated that as many as 22% of all new borns admitted to NICU develop low platelet counts. A platelet count of less than 150,000/mL is defined as thrombocytopenia irrespective of the age of the individual. Methods: All the neonates underwent necessary blood investigations like Complete blood counts, (including platelet counts, HB estimation, Red cell indices and PCV), Capsular Polysaccharide - reactive protein. (CRP), Peripheral Smear study, Blood culture, BT, CT, PT, aPPT, Anti-platelet Antibodies. Results: The prevalence of thrombocytopenia in our study was 28%. The proportion of severe thrombocytopenia among the neonatal thrombocytopenia, 11.2% in our study. Conclusions: It can be concluded that thrombocytopenia is very much common in among our NICU admissions. Septicemia is its most important and most common cause.